(untitled) (Circe de clásicos y modernos, 2018)
Plato outlines Philosophy as a discipline that surpasses other genres, like poetry and rhetoric, and suggests that they must be transformed and oriented towards objectivism, and dialectic would be a parameter in which refutation (ἔλεγχος) is of central importance. This paper examines this aspect in the Euthydemus, considering the figure of Marsyas in order to describe Socrates and to characterize platonic methodology. On this base it is posible to elucidate the relationship beween protreptic and dialectic in the construction of an antieristical model.